A pilot study on the sexual side effects of finasteride as related to hand preference for men undergoing treatment of male pattern baldness. (16th November 2012) - Motofei, Ion G.; Rowland, David L.; Georgescu, Simona R.; Baconi, Daniela L.; Dimcevici, Nicoleta P.; Paunica, Stana; Constantin, Vlad D.; Balalau, Cristian
Abstract : What's known on the subject? and What does the study add? Cerebral lateralization/specialization is a neurophysiological feature that has been documented regarding somatic, psychological and sexual functioning and that may be manifested in differences in hand preference, cognitive style, gonadal hormonal effects and possibly even sexual orientation. In this study we investigated a possible cerebral lateralization effect on sexual response for dihydrotestosterone, using finasteride as a hormone‐blocking compound. The results of this study differ substantially from other studies examining the effects of finasteride on sexual response, presumably due to the greater restrictions we placed on defining relevant sexual activity, to our alerting patients to both positive and negative sexual effects and to the fact that we assessed the effects separately in right‐handed vs left‐handed patients. Handedness, as a proxy for cognitive style and possible lateralization of effect/function, appears to be a relevant factor when considering the sexual effects of specific gonadal hormones. OBJECTIVE:   To investigate the relationships between pharmacologically induced deprivation of dihydrotestosterone, sexual arousal, libido and hand preference, by comparing the self‐reported sexual response prior to and during reception of the anti‐androgen finasteride in men undergoing treatment for male pattern baldness. PATIENTS AND METHOD:   In total, 33 sexually healthy Romanian men participated in this study.   Patients prospectively provided information regarding their sexual functioning (over 4 weeks), as measured by the International Index of Erectile Function (IIEF) prior to and after commencing treatment with 1 mg finasteride for male pattern baldness. RESULTS:   Overall IIEF scores as well as the erectile function, orgasmic function, sexual desire and overall satisfaction subscales showed group, treatment and group by treatment effects.   The intercourse satisfaction subscale showed group and group by treatment effects.   On most subscales, right‐handed men showed no effect or lower sexual function whereas left‐handed men reported no effect or improved sexual function, primarily. CONCLUSIONS:   These results suggest that the sexual effects of dihydrotestosterone deprivation may depend on handedness – a proxy variable that may represent cognitive style – which lends further support to the idea of two distinct neuroendocrine psychosexual axes.   They further suggest that detection of such sexual effects may be enhanced by using research methodologies and communication strategies that increase patients' sensitization to such effects.